2020
DOI: 10.18231/2394-5478.2018.0088
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and multidrug resistance in nosocomial isolates of Acinetobacter

Abstract: Purpose: To study the biofilm formation and to examine the correlation between antibiotic resistance and biofilm formation among the clinical isolates of Acinetobacter. Materials and Methods: A total of 43 isolates of Acinetobacter collected from samples like peripheral venous catheter tips, urine from Foley's catheter, central venous catheter tips and endotracheal tube aspirates were preserved and processed. The tube method was performed to qualitatively detect Biofilm production. Antimicrobial susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…The results of this study correlates with various other studies done by Uppe et al, Rewdiwala et al, Kaur et al, Sharma et al, [13,14,16,19] A. baumannii, K.pneumoniae and P. aeruginosa showed multiple drug resistance which in concordance with various other studies done by Baidya et al, Sharma et al, Amin et al, Tomar et al and Natham et al [7,19,20,21,22] . In the present study, B. cepacia isolates showed susceptibility towards levofloxacin, minocycline, meropenem and cotrimoxazole.…”
Section: Resultssupporting
confidence: 92%
“…The results of this study correlates with various other studies done by Uppe et al, Rewdiwala et al, Kaur et al, Sharma et al, [13,14,16,19] A. baumannii, K.pneumoniae and P. aeruginosa showed multiple drug resistance which in concordance with various other studies done by Baidya et al, Sharma et al, Amin et al, Tomar et al and Natham et al [7,19,20,21,22] . In the present study, B. cepacia isolates showed susceptibility towards levofloxacin, minocycline, meropenem and cotrimoxazole.…”
Section: Resultssupporting
confidence: 92%
“…In particular, Abidi et al showed that biofilm production was higher among MDR P. aeruginosa strains than in non-MDR strains [ 6 ]. Moreover, Amin et al found that the A. baumannii MDR strains produced more biofilm than the non-MDR ones [ 7 ]. The association between the MDR phenotype and biofilm production underlined the need to better investigate the resistance profiles of biofilm producing strains.…”
Section: Discussionmentioning
confidence: 99%
“…Abidi et al showed that biofilm production was higher among MDR Pseudomonas aeruginosa ( P. aeruginosa ) strains than non-MDR strains [ 6 ]. Moreover, Qayoom et al found that the Acinetobacter baumannii ( A. baumannii ) MDR produced more biofilm than the non-MDR ones [ 7 ]. Regarding Staphylococcus aureus ( S. aureus ), Manandhar et al associated biofilm production with Methicillin resistance [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(100%) (p<0.05) being the most frequent. Meanwhile, Abidi et al [35]and Amin et al [36] reported a higher incidence of MDR-biofilm formation in P. aeruginosa and the ACB complex, respectively. Considering the existence of a positive correlation between the prevalence of MDR-and XDR-phenotypes among biofilm formations, it would be worthwhile to further investigate the resistance profiles associated with biofilm-producing strains.…”
Section: Plos Onementioning
confidence: 99%